Deradelphous Cephalothoracoomphalopagus in kittens - case report - Rodrigues,V.C.C. (2021)
ABSTRACT The present report describes a case of conjoined twins of the cephalo-thoraco-omphalopagus deradelphous type in cats. A feline female was transferred to our veterinary hospital as an emergency for dystocic labor. The stillborn was subjected to radiographic evaluation, and a single skull and two complete distinct vertebral columns were found. Anatomopathological examination revealed that the twins presented the head, chest, and umbilicus as the main points of union and were classified as the cephalo-thoraco-omphalopagus type. In addition, the twins had unique and well-developed faces, which allowed them to be classified as deradelphous. This malformation is rare in domestic animals, and to the best of our knowledge, this type has not been reported in felines. Further studies are warranted on this embryonic alteration, primarily because its etiology remains unknown.